THE INFLUENCE OF ORGANIZATIONAL COMMITMENT, PERSONAL COST AND ETHICAL ENVIRONMENT ON INTENTION TO WHISTLEBLOWING - Abdillah Abdillah; Ratna Ayu Damayanti; Amiruddin Amiruddin (Contemporary Journal on Business and Accounting, 2021)
Purpose – This study aims to examine and analyze the effect of organizational commitment, personal cost and ethical environment on the intention to do whistleblowing on the State Civil Apparatus of the Makassar City Education Office. Design/methodology/approach – This study uses a quantitative approach. The data used is primary data. The analytical method used is multiple linear regression. Findings – The result of this study shows that organizational commitment and personal cost has no impact against the whistleblowing intention, meanwhile ethical environtment has impact against the whistleblowing intention. Originality – Collecting data in this study through questionnaires and conducted on 40 respondents who were civil servant of Makassar Educational Authorities. Keywords: Ethical Environtment, Organizational Commitment, Personal Cost, Whistleblowing Intention Paper Type Research Result